Characterization of the major altered leader sequence of late mRNA induced by SV40 deletion mutant d1-1811. - Haegeman, G (1979)
d1-1811 is a viable SV40 mutant with a 40 base pair deletion that includes the major wild-type capping site of late mRNA at map position 0.72. The late viral mRNAs induced by d1-1811 have now been further characterized by inversed S1-mapping analysis. The S1-resistant, 32P-labeled RNA fragments derived from the leader region were examined by fingerprinting and by analysis of RNase T2-generated 5'-terminal cap structures. The results show that most if not all of the mutant leader fragments analyzed have their 5' terminus to the left of the d1-1811 deletion site, i.e., closer to the origin of DNA replication. The major altered leader fragment is a continuous transcript from the DNA in the region 0.716 to 0.761 map unit and its 5' terminus has been precisely mapped at nucleotide L290. The observation that the cap structure of the major altered leader is only a minor cap species in wild-type late RNA suggests regulation in the use of different capping sites in SV40.